PERAN VIDEO MARKETING DALAM PENINGKATAN BRAND AWARENESS DAN KEPUTUSAN PEMBELIAN: STUDI KASUS PADA INDUSTRI MAKANAN DAN MINUMAN KOTA PONTIANAK - sulasti, Sulasti; Martono, Martono; Sani, Sani (Jurnal Ekonomi Integra, 2024)
By using brand awareness as a mediator, the study seeks to ascertain how video marketing affects consumer decisions in Pontianak City's food and beverage industries. Once the data passes the traditional assumption test and is deemed valid and reliable, the research employs a survey approach with path analysis. Video marketing is the dependent variable, purchasing decisions are the independent variable, and brand awareness is the mediating variable. sources of data using surveys and interviews. 60 consumers who had seen food and beverage vendors' promotional videos made up the research sample. The study's findings indicated that they agreed with every hypothesis. The entire 40% influence of brand recognition and video marketing on purchasing decisions is the most prominent exogenous variable on endogenous factors, and it is highly significant. In this study, the route analysis model can account for 91.4% of the diversity of data; the remaining 8.6% can be explained by other factors.